Molecular Mechanisms of Obesity-Induced Osteoporosis and Muscle Atrophy - Roy, Bipradas; Curtis, Mary E.; Fears, Letimicia S.; Nahashon, Samuel N.; Fentress, Hugh M. (Frontiers in Physiology, 2016)
Obesity and osteoporosis are two alarming health disorders prominent among middle and old age populations, and the numbers of those affected by these two disorders are increasing. It is estimated that more than 600 million adults are obese and over 200 million people have osteoporosis worldwide. Interestingly, both of these abnormalities share some common features including a genetic predisposition, and a common origin: bone marrow mesenchymal stromal cells. Obesity is characterized by the expression of leptin, adiponectin, interleukin 6 (IL-6), interleukin 10 (IL-10), monocyte chemotactic protein-1 (MCP-1), tumor necrosis factor-alpha (TNF-α), macrophage colony stimulating factor (M-CSF), growth hormone (GH), parathyroid hormone (PTH), angiotensin II (Ang II), 5-hydroxy-tryptamine (5-HT), Advance glycation end products (AGE), and myostatin, which exert their effects by modulating the signaling pathways within bone and muscle. Chemical messengers (e.g., TNF-α, IL-6, AGE, leptins) that are upregulated or downregulated as a result of obesity have been shown to act as negative regulators of osteoblasts, osteocytes and muscles, as well as positive regulators of osteoclasts. These additive effects of obesity ultimately increase the risk for osteoporosis and muscle atrophy. The aim of this review is to identify the potential cellular mechanisms through which obesity may facilitate osteoporosis, muscle atrophy and bone fractures.